Economic Contribution and Environmental Degradation Impact of Corn Expansion: A Case Study of Dompu Regency, Indonesia - Nurhidayah Nurhidayah; Ibrahim Ibrahim (Journal of Governance and Spatial Planning, 2026)
The expansion of corn production has been a major driver of economic growth in the region, but at the same time it poses a risk of environmental damage, especially in areas with high agricultural intensification such as Dompu Regency. The main problem in this study is the lack of clarity regarding the economic contribution and environmental impact of corn production on the welfare of the local community. This study aims to analyze the influence of two variables, namely the economic contribution of corn (X1) and the environmental impact of corn expansion (X2), on improving the socio-economic conditions of the community (Y). The method used is a correlational quantitative approach involving 100 respondents through a Likert scale questionnaire. The data were analyzed using descriptive statistics and multiple linear regression. The results show that X1 has a positive and significant effect on Y (p < 0.001), while X2 has no significant effect (p > 0.05). The resulting regression model was very strong (R² = 0.829), with the largest contribution coming from variable X1. These findings indicate that increased corn production has a real economic impact on the community, but this is not in line with the respondents' perception of the environmental impact, which they do not consider to be significant. This study implies that corn development in Dompu must continue to consider environmental sustainability even though the economic benefits are dominant.